Supply chain enhancement through product and vendor development programme - Wan Mahmood, Wan Hasrulnizzam; Mat Tahar, Nurulain; Ab Rahman, Mohd Nizam; Md Deros, Baba (Emerald Group Publishing Limited, 2011)
This paper aims to review the methods used by an automotive manufacturer in enhancing the supply chain management (SCM) system through a set up termed product and vendor development(PVD) programme. PVD was developed to eliminate problems faced due to late delivery and poor quality of supplies and availability of supplies at the lowest possible costs. The paper explores the step-by-step methodologies that have been employed by the PVD. Results overtime show that the PVD has improved the SCM system especially in the areas of quality and delivery services, other services and cutting costs that manufacturers had to face due to problems that arose in the shortcomings of the supply services. The PVD has managed to promote the localization programme and has also been able to establish qualified vendors through the structured vendor performance evaluation. Findings also establish that the PVD team is the key to success for development of the PVD programme. The paper presents an original discussion about viewing PVD programme from a successful automotive manufacturer. The structured PVD programme helps the teambetter understand the product development process involving supplier selection and supplier performance measure.